Masculinised jobs, feminised jobs and men's 'gender capital' experiences: Understanding occupational segregation in Australia. (June 2013) - Huppatz, Kate; Goodwin, Susan
Australia features a highly segregated workforce where certain occupational spaces appear to privilege particular gendered dispositions. While research on gender and work highlights the association between occupational segregation and gender inequality, conventional explanations of why men and women continue to be concentrated in different occupations, and in different roles within occupations, can be considered problematic. This article argues that we may be able to achieve a deeper understanding of gendered occupational segregation than previous explanations have offered by appropriating Bourdieu's concept, 'capital'. Drawing on qualitative research with Australian workers we explore men's 'gender capital experiences' within masculinised and feminised occupations. The article discusses how male, masculine and feminine embodiments can operate as capitals which may be accumulated and transacted, perpetuating horizontal gender segregation in the workforce but also vertical segregation within occupations. In doing so, we expand the work of feminist Bourdieusian scholars who have reworked Bourdieu's approach so that gender, as well as class, may be understood as a central form of stratification in the social order.